Design, Synthesis, and In Vitro Antiplatelet Aggregation Activities of Ferulic Acid Derivatives. (2nd April 2015) - Zhang, Peng-Xuan; Lin, Hang; Qu, Cheng; Tang, Yu-Ping; Li, Nian-Guang; Kai, Jun; Shang, Guanxiong; Li, Baoquan; Zhang, Li; Yan, Hui; Liu, Pei; Duan, Jin-Ao
Abstract : In order to discover new compounds with antiplatelet aggregation activities, some ferulic acid (FA) derivatives were designed and synthesized. The in vitro antiplatelet aggregation activities of these compounds were assessed by turbidimetric test. The results showed that the target compound7f had potent antiplatelet aggregation activity with its IC50 27.6 μ mol/L, and7f can be regarded as a novel potent antiplatelet aggregation candidate.